New public management and health reform in Kazakstan - Amagoh, Francis (2011)
Faced with limited resources, governments around the world ae sturggling to devise the most effective means to deliver basic health services. This is especially true for transititional countries, such as Kazakhstan, which gained independence from the Soviet Union in 1991. The country has embarked on a framework known as Kazakhstan 2030, which aims among other things, to improve the living standards of all Kazakhs by the year 2030. A number of reform agendas have been underway in the health sector. This article provides a brief history of Kazakhstan's healthcare reform efforts, and analyzes its most recent comprehensive health care reform, the National Program of Health Care Reform and Development for 2005-2010, within the context of new public management (NPM). The article juxtaposes aspects of the National Program of Health Care Reform and Development for 2005-2010 within the following elements of NPM: decentralization, competition, efficiency and quality, and civil society and partnerships. - Reproduced.
Keywords: Public administration -Kazakhstan; -Kazakhstan; Health services